IMPLEMENTATION OF DIGITAL MARKETING PLAN TO INCREASE BRAND AWARENESS SALON JAVE HAIRDRESSING - Kiki Nadila; Golan Hasan (Universitas Internasional Batam, 2022)
The author does practical work on the Salon Jave Hairdressing SMME business starting on September 19 2021 until November 30 2021. The location of the Salon Jave Hairdressing SMME is located in Windsor. Mr. Hartono's micro, small and medium enterprises need a digital marketing plan to improve and face competition with other competitors.The process carried out during this practical work, the author conducted a survey and collected data for analysis in the form of the background of Salon Jave Hairdressing SMME. After doing the analysis, the author found several obstacles faced then the author implemented a strategy so that Mr.Hartono's business could compete with the current market. The obstacle found is the lack of a sales system so that it takes time to improve and develop a sales system. The system is a Digital marketing plan.Salon Jave Hairdressing's micro, small and medium enterprises have implemented the results of the Digital Marketing Plan which was designed and developed by the author. The author has made advertisements posted on social media and also we had registed SMME Salon JaveHairdressing to Google Business Account so that many consumers know what promotions are currently in effect on SMME Salon Jave Hairdressing.